Activating Joy and Hope in Critical Literacies Instruction: Responding Pedagogically to Youth Skepticism in a YPAR Project. (November 2021) - Hendrix-Soto, Aimee
In the face of persistent racial injustice, critical literacy approaches to instruction frequently involve investigating and altering unjust racialized power structures through critical action. However, what happens when youth have become understandably skeptical of action for change? This analysis uses healing frameworks to explore the critical literacies of Black and Latinx youth in a youth participatory action research project that took place in the early days of the Trump administration, as well as the pedagogies employed. The salience and persistence of racial injustice in national politics and the local school district operated against youth's reserves of hope and belief in change work, introducing tension into a project focused on transformation. As a pedagogical response, the project's two White coteachers facilitated new pathways for critical literacies that involved joy, care, and new audiences. This response focused on joy in critical work and prompted some, though notably not all, youth to reengage with critical action and articulate hope for justice in their local worlds.